Analisis Keuangan Sebagai Dasar Pengambilan Keputusan Strategis Dalam Bisnis - Arinita, Rafina; Putri, Fitriani Sagita; Andini, Egi; Pratama, Aldy Arya (Universitas Pamulang, 2025)
This community service activity aims to improve the understanding of students at SMK IPTEK South Tangerang City regarding the importance of financial statement analysis in supporting business decision-making. The main problem faced by the partner is the lack of practical understanding of how financial reports can be strategically used in business. The implementation methods include interactive lectures and training covering basic concepts of financial statements, financial ratio analysis, and simple case studies for decision making. The results showed an increase in students' understanding of how to read financial statements and make business strategies based on the analysis. This program is expected to enhance students' readiness to face real business challenges in the future. Keywords: Financial analysis; Strategic decisions; Financial reports; Entrepreneurship education